Development and Validation of a Rapid Assessment Version of the Assessment Survey of Primary Care in China - Zhong, Chenwen; Huang, Junjie; Li, Lina; Luo, Zhuojun; Liang, Cuiying; Zhou, Mengping; Kuang, Li (Frontiers in Public Health, 2022)
Background Measuring quality of primary care has attracted much attention around the world. Our team has developed and validated an Assessment Survey of Primary Care (ASPC) for assessing quality of primary care in China. To facilitate the daily use of ASPC, this study aimed to develop and validate a rapid assessment version of ASPC (RA-ASPC) in China. Methods This is a multi-phase study on 21 experts and 1,184 patients from 12 primary care facilities in ten cities. Importance, representativeness, easy understanding, and general applicability of each item in ASPC scale were rated to select the top two ranked items for constituting RA-ASPC. Reliability of RA-ASPC was tested by calculating both Cronbach’s alpha and McDonald’s omega coefficients. Structural validity was assessed by exploratory and confirmatory factor analysis (EFA and CFA). Concurrent validity was performed by analysing the relationship between RA-ASPC and patient satisfaction. Discriminant validity was tested by assessing the difference of RA-ASPC scores between patients with or without family doctors. Results Ten items were selected for RA-ASPC. Both Cronbach’s alpha (0.74) and McDonald’s omega (0.73) suggested satisfactory internal consistency. In EFA, explained variance of RA-ASPC (72.6%) indicated its ability to measure quality of primary care in China. CFA indicators showed convincing goodness-of-fit (GFI=0.996, AGFI=0.992, CFI=1.000, NFI=0.980, RMR=0.022, and the RMSEA=0.000) for RA-ASPC. Positive association between RA-ASPC and patient satisfaction supported the concurrent validity of RA-ASPC. Patients with family doctors perceived higher quality of primary care than those without family doctors, indicating good discriminant validity of RA-ASPC scale. Conclusion The theoretical framework of RA-ASPC was in line with internationally recognized core functions of primary care. Good psychometric properties of RA-ASPC proved its appropriateness in assessing quality of primary care from patients’ perspectives in China.